Reducing methane production from stored feces of dairy cows by Asparagopsis taxiformis - Ramin, Mohammad; Chagas, Juana C. C.; Pal, Yash; Danielsson, Rebecca; Fant, Petra; Krizsan, Sophie J. (Frontiers in Sustainable Food Systems, 2023)
The objective was to evaluate whether methane (CH4) production from stored feces of cows previously supplemented with Asparagopsis taxiformis (AT) in their diet was lower compared with the feces of cows not supplemented with AT. We also investigated the possibility of further reducing CH4 production by adding AT to the stored feces of cows. Fecal samples were provided from a feeding trial (during two different periods) of four cows divided into two different groups. One group was supplemented with AT at a level of 0.5% of the total organic matter intake, and the other group was not supplemented with AT. A 2 × 2 factorial design was set in the laboratory for the incubation of feces. Fecal samples from the two groups of cows were divided into two subsamples receiving either no addition of AT or the addition of AT at a level of 0.5% of OM incubated. This resulted in four treatments with two replicates per period. The same design was repeated during period two. In total, 400 g of fresh fecal samples were incubated in 1 L serum bottles for 9 weeks at 39°C in a water bath. CH4 and total gas production were measured on days 1, 4, and 7 and subsequently every 2nd week until the end of the incubation period. Enteric CH4 production showed a significant reduction (61%) when AT was supplemented in the diet of dairy cows. We found that CH4 production from the feces of dairy cows supplemented with AT in their diet was only numerically lower (P = 0.61). Adding AT to the feces of dairy cows significantly reduced CH4 production from the feces by 44% compared with feces without AT. There were no differences observed in the bacterial and archaeal community profiles of fecal samples between cows fed AT and those not fed AT. This study concludes that the addition of AT to stored feces can effectively reduce CH4 production from the feces of dairy cows.